ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM CERPEN “BURUNG SENJA” KARYA WILSON NADEAK - Fathimatuz Zahra; Rochmat Tri Sudrajat; Mimin Sahmini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research contained about the analysis intrinsic element and moral values of short stories “Burung Senja” by Wilson Nadeak. Researchers chose a short story entitled “Burung Senja”. First, it has the value of life that can be used as an model by readers, such as the affection of children to parents, and loyalty to the couple life. Second, this short story has a complex storyline, diction and imagination of stories look realistic. Third, short story author is one of the man of letters figure from Indonesian, but not many people who know their works, so that the author wants to lift this short story through the research analysis. The aim of this research was to explain intrinsic element and moral values of short stories by Wilson Nadeak. The method in this research is the qualitative descriptive. Data in used as a source on this research is, one of the essays short stories by Wilson Nadeak’s published in a ”Mata yang Indah; Cerpen Pilihan Kompas 2001”. Based on the analysis shows if there are elements integrity foundation of a short story as works of literature prose, is: themes, grooves, figures and cement fors, the background/setting, the point of view of storytelling and mandate. Apart from that, researchers found moral values described by figures in a short story such as: loyalty, togetherness, love feeling and patience.